1991
DOI: 10.1177/002224299105500304
|View full text |Cite
|
Sign up to set email alerts
|

The Protection Motivation Model: A Normative Model of Fear Appeals

Abstract: Marketing researchers have questioned the use of the fear appeal, believing it to be too difficult to implement properly. AIDS, drug abuse, and other social problems have caused practitioners to return to the fear appeal, but with little direction from marketing theory. The protection motivation paradigm offers a prescriptive model to improve the effectiveness of the fear appeal. The authors propose and empirically test several changes to the PM model. Results indicate that fear appeals should present certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
197
2
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(217 citation statements)
references
References 19 publications
12
197
2
6
Order By: Relevance
“…PMT has received validation in a diverse array of behaviours, such as medical treatments (Mesters, Meertens, Kok, & Parcel, ), environmental hazards (Weinstein, ) and safer sex behaviours (Tanner, Hunt, & Eppright, ). Predictions of PMT have also been confirmed in empirical findings within the context of problematic substance use (Milne et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…PMT has received validation in a diverse array of behaviours, such as medical treatments (Mesters, Meertens, Kok, & Parcel, ), environmental hazards (Weinstein, ) and safer sex behaviours (Tanner, Hunt, & Eppright, ). Predictions of PMT have also been confirmed in empirical findings within the context of problematic substance use (Milne et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…PMT has demonstrated that fear influences individuals to seriously engage in protective behaviours (Rogers & Prentice‐Dunn, ). Fear has been indicated to be a key and necessary component in the cognitive appraisal process (Eppright, Hunt, Tanner, & Franke, ; Tanner et al, ). In the later version of PMT (Floyd et al, ; Rogers & Prentice‐Dunn, ), fear is situated as a mediator between threat and protection motivation, where its mediation is vital for increasing the intention to implement protective behaviours.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Some studies show that higher levels of health knowledge have a significant positive effect on information search and use (Moorman and Matulich 1993). Other articles report that prior knowledge and experience decrease preventive health behavior: consumers engage in maladaptive behavior—coping behavior that reduces one's fear without actually reducing health‐related dangers (Tanner, Hunt, and Eppright 1991, pp. 42–43).…”
mentioning
confidence: 99%
“…We also measured intentions with respect to behaviors people could adopt when with others (friends, family, and children) and that could change social norms regarding tobacco and smoking. We thus asked smokers if the tobacco pack they saw would “motivate them to hide it from their family, friends or children.” We asked non‐smokers if the tobacco pack they saw could provide a useful cue “to encourage their family and friends to quit.” Last, as a manipulation check, we measured whether PWL/text‐only warnings generated different levels of negative emotions and used the scale proposed by Witte () and Tanner, Hunt, and Eppright () to evaluate fright, tenseness, nervousness, anxiety, discomfort and disgust. We also checked that the branded pack differed on attractiveness with respect to the plain pack.…”
Section: Methodsmentioning
confidence: 99%
“…Thus smoking status seems to moderate PWLs effects. These weakened effects may be reinforced by the fact that few countries require efficacy and self‐efficacy messages (i.e., “stopping smoking reduces the risk of diseases”; “you CAN quit smoking”) in combination with PWLs, even though the literature recommends using affirming messages to prevent reactance (Hoek et al ; Tanner, Hunt, and Eppright ; Thrasher et al ).…”
Section: The Impact Of Tobacco Warningsmentioning
confidence: 99%